Nickel-Induced Reduced Graphene Oxide Nanoribbon Formation on Highly Ordered Pyrolytic Graphite for Electronic and Magnetic Applications - Luis-Sunga, Maximina; González-Orive, Alejandro; Calderón, Juan Carlos; Gamba, Ilaria; Ródenas, Airán; de los Arcos de Pedro, Maria Teresa; Hernández-Creus, Alberto; Grundmeier, Guido; Pastor, Elena; García, Gonzalo (ACS Applied Nano Materials)

AFM-IR investigation of thin PECVD SiO x films on a polypropylene substrate in the surface-sensitive mode - Müller, Hendrik; Stadler, Hartmut; de los Arcos de Pedro, Maria Teresa; Keller, Adrian; Grundmeier, Guido (Beilstein Journal of Nanotechnology)
AFM-IR investigation of thin PECVD SiOx films on a polypropylene substrate in the surface-sensitive mode

Thermophoretic Analysis of Biomolecules across the Nanoscales in Self-Assembled Polymeric Matrices - Liu, Ping; Schumann, Nils; Abele, Fabian; Ren, Fazheng; Hanke, Marcel; Xin, Yang; Hartmann, Andreas; Schlierf, Michael; Keller, Adrian; Lin, Weilin; Zhang, Yixin (ACS Applied Nano Materials)
Keywords: General Materials Science

Molecular Adhesion of a Pilus‐derived Peptide Involved in Pseudomonas aeruginosa Biofilm Formation on non‐polar ZnO Surfaces - Prüßner, Tim; Meinderink, Dennis; Zhu, Siqi; Orive, Alejandro G.; Kielar, Charlotte; Huck, Marten; Steinrück, Hans-Georg; Keller, Adrian; Grundmeier, Guido (Chemistry – A European Journal)
Bacterial colonization and biofilm formation on abiotic surfaces are initiated by the adhesion of peptides and proteins. Understanding the adhesion of such peptides and proteins at a molecular level thus represents an important step toward controlling and suppressing biofilm formation on technological and medical materials. This study investigates the molecular adhesion of a pilus‐derived peptide that facilitates biofilm formation of Pseudomonas aeruginosa, a multidrug‐resistant opportunistic pathogen frequently encountered in healthcare settings. Single‐molecule force spectroscopy (SMFS) was performed on chemically etched ZnO surfaces to gather insights about peptide adsorption force and its kinetics. Metal‐free click chemistry for the fabrication of peptide‐terminated SMFS cantilevers was performed on amine‐terminated gold cantilevers and verified by X‐ray photoelectron spectroscopy (XPS) and polarization‐modulated infrared reflection absorption spectroscopy (PM‐IRRAS). Atomic force microscopy (AFM) and XPS analyses reveal stable topographies and surface chemistries of the substrates that are not affected by SMFS. Rupture events described by the worm‐like chain model (WLC) up to 600 pN were detected for the non‐polar ZnO(11‐20) surfaces. The dissociation barrier energy at zero force ΔG(0), the transition state distance xb and bound‐unbound dissociation rate at zero force koff(0) for the single crystalline substrate indicate that coordination and hydrogen bonds dominate the peptide/surface interaction.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Electropolymerization of acrylic acid on steel for enhanced joining by plastic deformation - Duderija, B.; Sahin, F.; Meinderink, D.; Calderón-Gómez, J.C.; Schmidt, H.C.; Homberg, W.; Grundmeier, G.; González-Orive, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Dynamics of DNA Origami Lattices - Julin, Sofia; Keller, Adrian; Linko, Veikko (Bioconjugate Chemistry)
Keywords: Organic Chemistry; Pharmaceutical Science; Pharmacology; Biomedical Engineering; Bioengineering; Biotechnology

Large-Scale Formation of DNA Origami Lattices on Silicon - Tapio, Kosti; Kielar, Charlotte; Parikka, Johannes M.; Keller, Adrian; Järvinen, Heini; Fahmy, Karim; Toppari, J. Jussi (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Nanoparticle‐Based Formulations of Glycopeptide Antibiotics: A Means for Overcoming Vancomycin Resistance in Bacterial Pathogens? - Pothineni, Bhanu Kiran; Keller, Adrian (Advanced NanoBiomed Research)
Keywords: General Medicine

Effect of Ionic Strength on the Thermal Stability of DNA Origami Nanostructures - Hanke, Marcel; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Stability of DNA Origami Nanostructures in Physiological Media: The Role of Molecular Interactions - Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

High-speed AFM studies of macromolecular dynamics at solid/liquid interfaces - Keller, Adrian; Grundmeier, Guido (Reference Module in Chemistry, Molecular Sciences and Chemical Engineering)

Cation-dependent assembly of hexagonal DNA origami lattices on SiO2 surfaces - Pothineni, Bhanu Kiran; Grundmeier, Guido; Keller, Adrian (Nanoscale)
DNA origami nanostructures have emerged as functional materials for applications in various areas of science and technology. In particular, the transfer of the DNA origami shape into inorganic materials using...
Keywords: General Materials Science

UV-enhanced environmental charge compensation in near ambient pressure XPS - Müller, Hendrik; Weinberger, Christian; Grundmeier, Guido; de los Arcos de Pedro, Maria Teresa (Journal of Electron Spectroscopy and Related Phenomena)
Keywords: Physical and Theoretical Chemistry; Spectroscopy; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Radiation; Electronic; Optical and Magnetic Materials

Multiprotein Adsorption from Human Serum at Gold and Oxidized Iron Surfaces Studied by Atomic Force Microscopy and Polarization-Modulation Infrared Reflection Absorption Spectroscopy - Huang, Jingyuan; Qiu, Yunshu; Lücke, Felix; Su, Jiangling; Grundmeier, Guido; Keller, Adrian (Molecules)
Multiprotein adsorption from complex body fluids represents a highly important and complicated phenomenon in medicine. In this work, multiprotein adsorption from diluted human serum at gold and oxidized iron surfaces is investigated at different serum concentrations and pH values. Adsorption-induced changes in surface topography and the total amount of adsorbed proteins are quantified by atomic force microscopy (AFM) and polarization-modulation infrared reflection absorption spectroscopy (PM-IRRAS), respectively. For both surfaces, stronger protein adsorption is observed at pH 6 compared to pH 7 and pH 8. PM-IRRAS furthermore provides some qualitative insights into the pH-dependent alterations in the composition of the adsorbed multiprotein films. Changes in the amide II/amide I band area ratio and in particular side-chain IR absorption suggest that the increased adsorption at pH 6 is accompanied by a change in protein film composition. Presumably, this is mostly driven by the adsorption of human serum albumin, which at pH 6 adsorbs more readily and thereby replaces other proteins with lower surface affinities in the resulting multiprotein film.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Adsorption of Ferritin at Nanofaceted Al2O3 Surfaces - Pothineni, Bhanu K.; Kollmann, Sabrina; Li, Xinyang; Grundmeier, Guido; Erb, Denise J.; Keller, Adrian (International Journal of Molecular Sciences)
The influence of nanoscale surface topography on protein adsorption is highly important for numerous applications in medicine and technology. Herein, ferritin adsorption at flat and nanofaceted, single-crystalline Al2O3 surfaces is investigated using atomic force microscopy and X-ray photoelectron spectroscopy. The nanofaceted surfaces are generated by the thermal annealing of Al2O3 wafers at temperatures above 1000 °C, which leads to the formation of faceted saw-tooth-like surface topographies with periodicities of about 160 nm and amplitudes of about 15 nm. Ferritin adsorption at these nanofaceted surfaces is notably suppressed compared to the flat surface at a concentration of 10 mg/mL, which is attributed to lower adsorption affinities of the newly formed facets. Consequently, adsorption is restricted mostly to the pattern grooves, where the proteins can maximize their contact area with the surface. However, this effect depends on the protein concentration, with an inverse trend being observed at 30 mg/mL. Furthermore, different ferritin adsorption behavior is observed at topographically similar nanofacet patterns fabricated at different annealing temperatures and attributed to different step and kink densities. These results demonstrate that while protein adsorption at solid surfaces can be notably affected by nanofacet patterns, fine-tuning protein adsorption in this way requires the precise control of facet properties.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Superstructure-dependent stability of DNA origami nanostructures in the presence of chaotropic denaturants - Hanke, Marcel; Dornbusch, Daniel; Tomm, Emilia; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (Nanoscale)
The structural stability of DNA origami nanostructures in various chemical environments is an important factor in numerous applications, ranging from biomedicine and biophysics to analytical chemistry and materials synthesis. In...
Keywords: General Materials Science

Open time studies of cold curing polyurethane adhesives using a standardized spatula test setup suitable for near-production conditions - Mahnel, Sabrina; Bannert, Franz; Zimmermann, Johannes; Grunder, Sergio; Demmig, Martin; Lomolino, Silvia; Grundmeier, Guido (International Journal of Adhesion and Adhesives)

Monitoring Polymeric Fouling in a Continuous Reactor by Electrochemical Impedance Spectroscopy - Neßlinger, Vanessa; Rust, Sören; Atlanov, Jan; Pauer, Werner; Grundmeier, Guido (Chemie Ingenieur Technik)
Abstract Monitoring early stages of polymeric deposit formation and its prevention were studied by in‐situ electrochemical impedance spectroscopy (EIS) in a continuously operating reactor employed for polymer production. An EIS flow cell was designed and employed during the emulsion polymerization of vinyl acetate. The electrochemical analysis of the complex impedance at the solution/reactor interface allows the time‐resolved detection of film formation processes. In comparison to oxide‐covered stainless steel, an anti‐adhesive sol‐gel coated alloy showed a significant inhibition of poly(vinyl acetate) fouling. The EIS‐based approach proved to be a valuable tool for monitoring both thin barrier film performance and fouling processes under harsh process conditions.